MUCOSAL CHANGES RESULTING FROM BETEL QUID AND TOBACCO CHEWING - PRATISHTA JAIN; ARVIND M (International Journal of Pharma and Bio Sciences, 2014)
Oral cancer, a malignant neoplasm arising from dysplastic epithelium most commonly arises from pre-existing potentially malignant disorders (PMD). Tobacco in various forms is the commonest cause for the genesis of PMD. In the Indian subcontinent, use of smokeless tobacco is very high and contributes to the development of PMD and oral cancers. Betel quid and tobacco are used in various forms in different parts of India. Quid is a product obtained by mixing basic ingredients like tobacco, areca nut to which other constituents like slaked lime are added. These ingredients are then placed in a betel leaf and placed in the oral mouth in contact with the mucosa and chewed. This habit of betel quid usage and chewing tobacco leads to lot of oral mucosal changes. These changes should be identified by the dentist in the early stages and suitable treatment initiatives should be taken to prevent oral pre cancer and cancer